A Novel Data AggregationTechnique for Removing Redundant Data in Hadoop - SV, Uday Shankar; Naik, Anvesh; CK, Manoj; B, Praveen; BR, Yadush (International Journal of Computer Sciences and Engineering, 2025)
Hadoop is the software framework which was developed by Apache Software Foundation.Hadoop framework is written in java with purpose to handle large amount of data. Hadoop manages huge volume of data.Hadoop runs the task under the MapReduce algorithm. MapReduce is a programming model suitable for processing of huge data. MapReduce framework has two phase, map phase and reduce phase.a mapredce job is usually splits the input data set into independent chunks,which is done by map phase.the framework sorts the output of the map which are input to reduce framework. To running frequent itemset require more resource and time consuming. To overcome this problem here we implementing the nobel data aggregation technique.